2004
DOI: 10.1177/0092055x0403200107
|View full text |Cite
|
Sign up to set email alerts
|

Using Focused Web-Based Discussions to Enhance Student Engagement and Deep Understanding

Abstract: To increase student engagement and enhance critical thinking and deep understanding, I supplemented weekly seminar meetings with focused Web-based discussions of issues in a “Race and Education” senior sociology seminar. These Web-based discussions were structured by specific questions and discussion roles. Before seminar, Staters posted on the course Web site the most important thing they learned from a reading, describing what was most difficult, and raising new sociological questions. After seminar, Respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 20 publications
(5 reference statements)
1
40
0
Order By: Relevance
“…For the reasons listed above, theoretically roles are suggested to increase several important factors including student participation (Tagg 1994), metacognition (Persell 2004), interaction between learners (Hara et al 2000), integration of discourse (Strijbos et al 2004) and knowledge construction ). However, empirical research on roles has produced conflicting results about their effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…For the reasons listed above, theoretically roles are suggested to increase several important factors including student participation (Tagg 1994), metacognition (Persell 2004), interaction between learners (Hara et al 2000), integration of discourse (Strijbos et al 2004) and knowledge construction ). However, empirical research on roles has produced conflicting results about their effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…the critical conditions for learning through social interaction in the domains of educational psychology (Nystrand & Gamoran, 1991;Pintrich & De Groot, 1990;Vygotsky, 1978) and technology-based learning environments (Hannafin et al, 1996;Hmelo et al, 1999;Persell, 2004). Okolo and Ferretti (1996) found that when students work in virtual communities, they share the process of constructing ideas, instead of working on their own.…”
Section: Ering How To Engage What Helps and What Hinders; 2) Developmentioning
confidence: 99%
“…Faculty and administrators increasingly promote active learning in which students learn by doing something (e.g., Christiansen & Fischer, 2010;Godfrey, 2015;Obach, 2009;Pedersen, 2010;Persell, 2004), while the best practices of online learning in social science urge instructors to "increase motivation and engagement" among learners (McKinney, 2010, p. 1). In addition to fostering active rather than passive students, engaged learning may facilitate the development of analytical skills for higher-order learning.…”
Section: Engaging With Our Learnersmentioning
confidence: 99%
“…In their review of best practices of online discussions, Boettcher and Conrad (2010, p. 37) suggest that successful student posts should invite responses, questions, discussions, and reflection. Persell (2004) finds that online discussions produce greater participation, engagement, and interaction compared to the traditional course design. Students spend more time analyzing and reflecting on the questions being posed before providing written feedback and are more likely to feel as though they are part of a classroom dialogue (Clark-Ibáñez & Scott, 2008).…”
Section: Engaging With Our Learnersmentioning
confidence: 99%